Biodegradability and formulation of triclosan-degrading and plant-growth-promoting Pseudomonas sp. MS45 - MERRY KRISDAWATI SIPAHUTAR (Society for Indonesian Biodiversity, 2024)
Abstract. Sipahutar MK. 2024. Biodegradability and formulation of triclosan-degrading and plant-growth-promoting Pseudomonas sp. MS45. Biodiversitas 25: 2980-2992. This study presents the isolation of Pseudomonas sp. MS45, a microorganism that can consume triclosan (TCS) as its only carbon and energy source, leading to its detoxification. The rarity of a toxicity study of TCS before and after biodegradation treatment is addressed in this study. Allium cepa's genotoxicity exposed TCS's cytotoxicity, generating multiple damaged chromosomes, in contrast to the insignificant consequences of its broken-down metabolites. The study also optimized the different kinetic parameters for TCS-specific biodegradation and Pseudomonas sp. MS45-specific growth. The biodegradation pattern followed the Michaelis-Menten model with a maximum specific biodegradation rate (Vmax) of 0.01 µmole h-1 mg cell protein-1 and a half saturation constant (Ks) of 21.98 µM. The growth pattern followed the Haldane model with a maximum specific growth rate (µmax) of 0.03 h-1, half saturation constant (Ks) of 4.56 µM, and TCS inhibition constant (Ki) of 32.81 µM. In addition to its TCS-degrading ability, Pseudomonas sp. MS45 also possesses various plant growth promotion traits, and it was incorporated into two solid carrier formulations: vermiculite and rice bran. The study found that vermiculite, especially with PEG, was the most consistent formulation for Pseudomonas sp. MS45, in terms of maintaining bacterial survival and TCS-degrading ability. This study marks the initial report on the biodegradation and formulation of TCS-destroying and Plant-Growth-Promoting (PGP) Pseudomonas sp. MS45, offering promising implications for environmental and agricultural applications.